Plant Defense Networks against Insect-Borne Pathogens - Ye, J.; Zhang, L.; Zhang, X.; Wu, X.; Fang, R.
Upon infection with insect-borne microbial pathogens, plants are exposed to two types of damage simultaneously. Over the past decade, numerous molecular studies have been conducted to understand how plants respond to pathogens or herbivores. However, investigations of host responses typically focus on a single stress and are performed under static laboratory conditions. In this review, we highlight research that sheds light on how plants deploy broad-spectrum mechanisms against both vector-borne pathogens and insect vectors. Among the host genes involved in multistress resistance, many are involved in innate immunity and phytohormone signaling (especially jasmonate and salicylic acid). The potential for genome editing or chemical modulators to fine-tune crop defensive signaling, to develop sustainable methods to control insect-borne diseases, is discussed.
Keywords: INSECT-BORNE PATHOGEN; JASMONATE; PATTERN-TRIGGERED IMMUNITY; PLANT DEFENSE; TRIPARTITE INTERACTIONS